Psychological wellbeing in Chinese university students: insights into the influences of academic self-concept, teacher support, and student engagement - Zhang, Hua (Frontiers in Psychology, 2024)
Objective: This study investigates the complex interplay between academic self-concept, teacher support, student engagement, and psychological well-being among Chinese university students. We aimed to elucidate the mediating role of student engagement in these relationships.Method: A sample of 597 Chinese undergraduate students from diverse universities participated in the study. We employed structured questionnaires to assess academic self-concept, teacher support, student engagement, and psychological well-being. Confirmatory factor analyses and structural equation modeling were used to test our hypothesized model.Structural equation modeling indicated that the partial mediation model, which considered both direct and indirect effects, outperformed full mediation and direct effect models. Student engagement significantly mediated the relationships between academic self-concept, teacher support, and psychological well-being. Importantly, teacher support demonstrated a direct impact on psychological well-being, even when accounting for the mediating role of student engagement.This study underscores the pivotal role of student engagement as a mediator in the relationship between academic self-concept, teacher support, and psychological well-being among Chinese university students. While student engagement plays a substantial mediating role, our findings also recognize the persistent direct influence of teacher support on psychological wellbeing. These insights have implications for educators and policymakers aiming to enhance the well-being of university students by fostering positive academic self-concept and teacher support while recognizing the importance of student engagement.